New insights into a complex fungal pathogen: the case of Paracoccidioides spp (2016)
ABSTRACT: Paracoccidioidomycosis is a systemic mycosis endemic to Latin America, with Paracoccidioides brasiliensis and P. lutzii being the causal agents of this disorder. Several issues have been raised in the 100 years since its discovery and in this article we discuss features of this fascinating fungal pathogen, including its biology, eco-epidemiology and aspects of its pathogenicity. We also consider some of its virulence determinants, the most recent advances in the study of its metabolic pathways and the molecular and genetic research tools developed for this research. We also review the animal models used to study host-fungal interactions and how the host defence mechanisms against this pathogen work.